Comparative genomics of quinolone‐resistant and susceptible Campylobacter jejuni of poultry origin from major poultry producing European countries (GENCAMP). Issue 5 (16th May 2018) - Leekitcharoenphon, Pimlapas; Garcia‐Graells, Cristina; Botteldoorn, Nadine; Dierick, Katelijne; Kempf, Isabelle; Olkkola, Satu; Rossi, Mirko; Nykäsenoja, Suvi; Malorny, Burkhard; Stingl, Kerstin; Battisti, Antonio; Franco, Alessia; et al.
Abstract : A total of 502 Campylobacter jejuni isolates from poultry in 12 different European countries (10 of them the largest poultry production countries in Europe) were whole genome sequenced to examine the genomic diversity of fluoroquinolone resistant (FQ‐R) and susceptible (FQ‐S) C. jejuni across the poultry producing European countries and to determine whether the emergence of fluoroquinolone resistance among C. jejuni is related to the transmission through countries or to the selection through fluoroquinolone use in the individual countries. A high genomic diversity was observed. The isolates clustered in four main clusters. All trees revealed that the isolates were clustered according to the presence/absence of the gyr A mutations causing fluoroquinolone resistance and ST‐types. The cgMLST trees of only FQ‐R and FQ‐S isolates showed that isolates from the same country of origin were distributed into multiple clusters similarly to the trees combining FQ‐R and FQ‐S isolates. The different phylogenetic methods, ranging from single nucleotide polymorphisms analysis to gene‐by‐gene approaches such as rMLST, cgMLST, wgMLST and core genome tree, provided concordant results, but it is not known which is the most accurate method for identifying the country of origin of the isolates. Allele frequency analysis of isolates under this study and a selection of previously published C. jejuni genomes in ENA showed association of geographical origin of poultry C. jejuni populations between Romania‐Poland, Italy‐Germany‐England, Portugal‐The Netherlands and USA‐Luxemburg. Allele frequency and phylogenetic analysis indicated that the isolates from Finland were genetically different from C. jejuni populations from other European countries included in this study. Trade pattern and antimicrobial use in livestock were not significantly associated with allele frequency or populations of C. jejuni, but data available to investigate these associations were limited.